Bedtime for Frances - Hoban, Russell; Williams, Garth (New York : Scholastic, 1960)
Frances finds it difficult to go to sleep with the strange noises and menacing shapes that seem to fill her room after dark.
3.4
K-3
Keywords: Badgers -- Fiction; Bedtime -- Fiction; Fear of the dark -- Fiction; Frances (Fictitious character : Hoban) -- Fiction; Badgers -- Fiction; Bedtime -- Fiction; Fear of the dark -- Fiction; Frances (Fictional character : Hoban) -- Fiction